The role of antioxidants in improving biodiesel's oxidative stability, poor cold flow properties, and the effects of the duo on engine performance: A review - Amran, N.A. (Elsevier Ltd, 2022)
Global competitiveness thrives on meeting energy demand, and the need to counter the effects of environmental threads dispatched by the combustion of fossil fuels became the driving forces that upended the renewed commitment and growing interest in renewables. Alternatively, green energy provides a twofold solution to energy and environmental crisis in a sustainable, economically viable, and eco-friendly manner. However, energy from biomass, especially biodiesel is considered an attractive substitute for mineral diesel, with the proficiency of meeting future energy demand. Inevitably, biodiesel exhibits poor cold flow properties leading to plugging and gumming of filters, whereas oxidation stability results in sediments and gum formation. These effects present a legitimate concern to producers and the automotive sector. Many reviews on the use of antioxidants to improve biodiesel's cold flow and oxidative stability flooded the literature independently. Yet, a review encompassing the factors inducing biodiesel's poor cold flow, oxidation stability, their effects on engine performance, and the inhibitory role of antioxidants appears vacant. Hence, this paper put together the above-stated aspects, with the first part discussing the factors initializing and accelerating oxidation, the mechanism of oxidation, and biodiesel cold flow were subsequently discussed. Next, the inhibitory functions of antioxidants on biodiesel's oxidation stability and poor cold flow were also explained. Finally, this review reflects on the research trends and sustainability prospects of using antioxidants for improving biodiesel's poor flow and oxidative stability without hindrance to the engine system. Â© 2022 The Authors